Total MRI burden of cerebral vessel disease correlates with the progression in patients with acute single small subcortical strokes. Issue 1 (3rd December 2018) - Jiang, Jingwen; Huang, Xiaojun; Zhang, Yu; Deng, Weiping; Shen, Fanxia; Liu, Jianrong
Abstract: Background: The patients of single small subcortical strokes (SS) commonly have neurological worsening with risk factors, and mechanisms remain unclear. Asymptomatic lacunes, white matter lesions, cerebral microbleeds, and enlarged perivascular spaces are MRI markers of cerebral small vessel disease (cSVD). Previous studies mostly explored the association between the neurological deterioration and presence of above markers separately. The relationship between progressive single small SS and the simultaneous presence of multiple markers of cSVD has not been fully identified. We aimed to investigate whether total burden of cSVD detected with MRI was associated with progressive small SS in this study. Methods: Patients with single small SS (2.0 cm in diameter) were prospectively recruited during January 2016 and May 2018. Progression was defined as worsening by ≥1 point in National Institutes Health Stroke Scale (NIHSS) motor score within 72 hr from onset. The presence and burden of cSVD were determined by brain MRI, producing a score between 0 and 4. Besides, the patients' characteristics, clinical data, medical treatments during hospitalization stay were collected and statistically analyzed. Associations with progression were tested with forward stepwise regression analyses. Results: Fifty‐seven (35.6%) patients underwent progression. No significant difference was observed in the distribution of any single vascular risk factor and its related laboratory data among these patients. After adjustment for age, sex, NIHSS score at admission, and time from stroke to MRI in separate models, severe WMHs (OR = 4.892; 95% CI = 2.011–11.904, p = 0.016), moderate‐ and high‐grade basal ganglia EPVS (OR = 2.970; 95% CI = 1.861–6.121, p = 0.009), and total cSVD score (OR = 3.359; 95% CI = 2.016–5.599, p = 0.010) were associated with progression. Conclusion: This study demonstrated that total MRI cSVD burden was independently associated with progression after single small subcortical strokes. Abstract : In our study, 35.6% of patients with subcortical stroke showed progression in the first 72 hr after stroke onset. Severe WMHs and moderate‐ and high‐grade basal ganglia EPVS were associated with increased odds of progression in subcortical stroke patients. Total burden of cSVD was accompanied by neurological deterioration in single subcortical stroke patients.